Fretting behavior of the AISI 304 stainless steel under different atmosphere environments. (August 2015) - Esteves, M.; Ramalho, A.; Ramos, F.
Abstract: The response of homologous pairs of AISI 304 stainless steel to fretting in various conditions was studied on a linear reciprocating tribometer with sphere-on-flat contact. The study was focused on the behavior of the contact under different atmospheres (nitrogen and oxygen), displacement (20–60 µm) and relative humidity (10–85%). Evolution was assessed by friction and friction-dissipated energy regarding the wear, measured by 3D profilometry and optical microscopy. The oxidation rates were also evaluated by SEM and Raman spectroscopy. Atmosphere composition directly influences the oxidation process, consequently the fretting regimes and wear, although the nature of the oxides is defined by the availability of O2 and H2 O. Highlights: Homologous pairs of AISI 304 stainless steel was tested under fretting contact. The effect of humidity was evaluated from 10 to 85% RH. Environment reactivity was studied considering oxygen and nitrogen atmospheres. Archard model and friction energy based model were used to characterize the wear.